The “Grammar Police” Phenomenon in English Use: The Impact of Informal English Corrections on PBI UINSU Students’ Self-Confidence - Siregar, Deasy Yunita; Harahap, Syasi Aulya; Zawhara, Zawhara; Damanik, Denaida Hidayah; Ariela, Diva Nahda; Sherina, Dea (MUDABBIR Journal Research and Education Studies, 2025)
The “Grammar Police” phenomenon, in which people fix grammar faults in casual communication without being asked, has emerged as a result of the widespread usage of English in informal contexts. Even while grammatical correction is a crucial component of learning a language, improper correction in casual settings can have an impact on students’ emotional states and self-esteem. This study looks into how students in the State Islamic University of North Sumatra (UINSU) English Education Study Program (PBI) feel about themselves after receiving informal grammar correction. 21 PBI students who were chosen by convenience sampling participated in a survey as part of a quantitative research design. A 13-item Likert-scale questionnaire was used to gather data, and descriptive statistics were used for analysis. The results demonstrate that students’ confidence and willingness to use English informally are negatively impacted by informal grammar corrections, which frequently cause emotions of unease, anxiety, and dread of making mistakes. Additionally, students favor personalized, courteous, and encouraging grammar feedback. The study comes to the conclusion that maintaining students’ confidence in casual English speaking requires sympathetic and context-appropriate grammar correction.